ANALISA PENGARUH BENTUK IMPELLER TERHADAP PERFORMA POMPA SENTRIFUGAL DOUBLE SUCTION TYPE VENUS 1-900.1000 - Firmansyah, Rifqi; Suhendra, Bobie (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
The impeller wheel is an important component of centrifugal pumps, which need to get importantattention starting from designing and modeling impeller shapes. This is very influential on theperformance of the pump. This study aims to determine the exact model of the impeller in theinstaller in parallel and to maintain the balance of the pump working operation with time. Themethod used is a comparative system of pump impeller models in order to improve pumpperformance optimally. From the results of this study that the pump with a discharge of 3.1 m3/sobtained optimum results with a pump head of 281 meters and an efficiency of 88% and dimensionsof the blade width of 22.5 cm for the double suction pump type.